Effect of dimensional parameters on warpage of injection-molded plastic part using response surface methodology - Mohd Nasri, Md Salim (2009)
This thesis discusses the effect of dimensional parameters on warpage of injection-molded plastic part using response surface method. The objectives of this thesis are to investigate the effect of dimensional parameter on warpage, to develop prediction first and second mathematical model for warpage of plastic part using response surface method. A thin plastic part model is used in the analysis. To achieve minimum warpage, optimum process condition dimensional parameters are determined. X dimension, Y dimension and Z dimension are used as variables. The most important input parameter in this experiment is Z dimension (wall thickness) which is affecting the warpage of the plastic part. The others input also must be considered. Use the different value of X dimension, Y dimension and Z dimension to determine different value of warpage. The design of experiment that use in this experiment is three level full factorial designs. Finite element analysis using MoldFlow is done to determine experimental value of warpage. Response surface methodology is used to predict the warpage value based on finite element result and suitable predictive model is selected based on percentage of error comparison then optimization process using response surface method is done and the optimum dimensional parameters with minimum warpage value is obtained.